Attracting Foreign Direct Investment : What Can South Asia's Lack of Success Teach Other Developing Countries? - Gould, David M. (World Bank, Washington, DC, 2014)
Like many other developing countries, South Asian nations have been experiencing increased foreign direct investment inflows over the past decade as developing countries get a larger share of cross-border investments that were once sent to developed countries. Nonetheless, South Asia's inflows of foreign direct investment remain the lowest relative to gross domestic product among developing country regions. Why are South Asia's foreign direct investment inflows so low and what lessons can be drawn for developing countries as a whole? The analysis in this paper uses a novel empirical model that accounts for possible trends in convergence in the ratio of foreign direct investment to gross domestic product between countries and cross-sectional data for 78 countries from 2000 to 2011. The sample contains 52 developing countries. The analysis finds that two key factors are at work -- high overall regulatory restrictions on foreign direct investment and specific restrictions placed on doing business with other countries. These factors include overall trade restrictiveness, which reduces the benefits to cross-border investments, and weak institutions to protect foreign investors and facilitate investment. Nonetheless, the potential for faster growth in intra- and inter-regional foreign direct investment flows is significant. The main factors leading to this conclusion are South Asia's current low levels of foreign direct investment, the many unexploited opportunities for embodied knowledge transfer, and supply-chain linkages. The overall lessons for developing countries are that liberalizing policy constraints in both trade and foreign investment, keeping corporate tax rates modest, and improving governance and transparency could help to substantially improve foreign direct investment flows.